The Epistemic Cultures of the Digital Humanities and Their Relation to Open Science: Contributions to the Open Humanities Discourse - Barrocas Ferreira, Beatriz; Borges, Maria Manuel (Central European Journal of Educational Research, 2022)
The epistemic cultures approach exposes the different ways knowledge production channels are built up among the various fields of study. In revealing these differences, the fragmentation of science can be clearly seen. Digital humanities is one such field. It is an inter- and transdisciplinary field, composed of diverse epistemic cultures and marked by distinct knowledge production practices. In the current landscape of scholarly communication, namely the open science paradigm, open practices have been at the forefront of conversation and research. The discourse’s true focus, however, is more along the lines of the epistemic cultures of the hard sciences, meaning that it does not fully consider other domains of knowledge. Thus, through a literature review, this study aims to frame the digital humanities’ epistemic cultures in the discourse of open science. The conclusion is, a conversation needs to be had specifically about the openness of knowledge, also considering other epistemic cultures’ diversity of scholarly communication practices. This would include the humanities. While simultaneously opening up this discourse, it is considered that digital humanities can also contribute to its consolidation.